2019
DOI: 10.1186/s12859-019-2739-z
|View full text |Cite
|
Sign up to set email alerts
|

Extracting predictors for lung adenocarcinoma based on Granger causality test and stepwise character selection

Abstract: Background Lung adenocarcinoma is the most common type of lung cancer, with high mortality worldwide. Its occurrence and development were thoroughly studied by high-throughput expression microarray, which produced abundant data on gene expression, DNA methylation, and miRNA quantification. However, the hub genes, which can be served as bio-markers for discriminating cancer and healthy individuals, are not well screened. Result Here we present a new method for extracting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…According to mass spectrometry (MS) analysis, 15 proteins involved in a variety of biological process, including protein degradation, cell cycle, transcriptional regulation, stress factor, RNA splicing, and protein degradation, were identified as SIRT7 interacting candidates ( Figures 1 C and 1D). These genes in black were reported to interact with SIRT7 among the previous researches ( Fan et al., 2019 ; Grob et al., 2009 ; Iyer-Bierhoff et al., 2018 ; Jiang et al., 2017 ; Qi et al., 2018 ), and the rest need to be verified by IP methods. USP39, an SR-related protein and deubiquitinating enzyme, was detected in the SIRT7 pull-down products, suggesting that USP39 might interact with SIRT7.…”
Section: Resultsmentioning
confidence: 83%
“…According to mass spectrometry (MS) analysis, 15 proteins involved in a variety of biological process, including protein degradation, cell cycle, transcriptional regulation, stress factor, RNA splicing, and protein degradation, were identified as SIRT7 interacting candidates ( Figures 1 C and 1D). These genes in black were reported to interact with SIRT7 among the previous researches ( Fan et al., 2019 ; Grob et al., 2009 ; Iyer-Bierhoff et al., 2018 ; Jiang et al., 2017 ; Qi et al., 2018 ), and the rest need to be verified by IP methods. USP39, an SR-related protein and deubiquitinating enzyme, was detected in the SIRT7 pull-down products, suggesting that USP39 might interact with SIRT7.…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, using the novel Bayesian hierarchical Cox proportional hazards model, most of the 14 prognostic genes we found can be explained in terms of basic study and population study. It is reported that CPS1, IGFBP3, MCM5, MCM7, NT5E, PLK1, PTTG1, SERPINB5, TXNRD1 and TYMS were associated with the prognosis of lung adenocarcinoma or non-small cell lung cancer, which was also included in our 14 genetic findings 27 36 . Basic studies found that NME4 and POLR3G were related to tumorigenesis and the progression of lung adenocarcinoma 37 , 38 .…”
Section: Discussionmentioning
confidence: 79%
“…e occurrence and development of cancer are often accompanied by complex interactions between genes and changes in their products. is complexity may be one of the main obstacles hindering clinical diagnosis [32]. Nowadays, with the rapid development of high-throughput sequencing technology and the reduction of costs, the biomedical field has accumulated massive amounts of data.…”
Section: Applicationsmentioning
confidence: 99%